Bone marrow PMN-MDSCs and neutrophils are functionally similar in protection of multiple myeloma from chemotherapy - Ramachandran, Indu R.; Condamine, Thomas; Lin, Cindy; Herlihy, Sarah E.; Garfall, Alfred; Vogl, Dan T.; Gabrilovich, Dmitry I.; Nefedova, Yulia (Cancer letters, 2016)
•Myeloid cells play a critical role in regulation of myeloma growth.•PMN-MDSCs and neutrophils equally protect myeloma cells from chemotherapy.•PMN-MDSCs and neutrophils mediate chemoprotective effect through soluble factors. Multiple myeloma (MM) is an incurable cancer of plasma cells localized preferentially in the bone marrow (BM). Resistance to chemotherapy represents one of the main challenges in MM management. BM microenvironment is known to play a critical role in protection of MM cells from chemotherapeutics; however, mechanisms responsible for this effect are largely unknown. Development of MM is associated with accumulation of myeloid-derived suppressor cells (MDSCs) mostly represented by pathologically activated relatively immature polymorphonuclear neutrophils (PMN-MDSCs). Here, we investigated whether PMN-MDSCs are responsible for BM microenvironment-mediated MM chemoresistance. Using in vivo mouse models allowing manipulation of myeloid cell number, we demonstrated a critical role for myeloid cells in MM growth and chemoresistance. PMN-MDSCs isolated from MM-bearing host are immunosuppressive and thus, functionally distinct from their counterpart in tumor-free host neutrophils. We found, however, that both PMN-MDSCs and neutrophils equally promote MM survival from doxorubicin and melphalan and that this effect is mediated by soluble factors rather than direct cell–cell contact. Our data indicate that targeting PMN-MDSCs would enhance chemotherapy efficacy in MM.